A Decolonial Africa(n)-Centered Psychology of Antiracism. Issue 4 (December 2021) - Malherbe, Nick; Ratele, Kopano; Adams, Glenn; Reddy, Geetha; Suffla, Shahnaaz
Coloniality represents the contemporary patterns of power and domination that emerged in the late 15th century during the so-called classic era of colonialism. Although much of psychology and psychological thought has adhered to the logic of coloniality, there is also a considerable body of work that has sought to decolonize psychology. It is within this latter tradition of decolonizing psychology—which seems to have gained increasing attention in recent years—that we situate this article and its attempt to articulate a decolonial Africa(n)-centered psychology that addresses itself to antiracism. While we concede that there are myriad ways by which to practice and theorize such a psychology, we focus specifically on collective antiracist struggle and everyday antiracist resistance. We conclude by considering questions of universalism and epistemology as they relate to a decolonial Africa(n)-centered psychology of antiracism.